Design of Solar dish concentration by using MATLAB program and Calculation of geometrical concentration parameters and heat transfer - Yaseen. H. Mahmood; Mayadah K h. Ghaffar (Tikrit Journal of Pure Science, 2023)
Renewable energy sources plays an important role in electricity generation. Various renewable energy sources like wind, solar, geothermal, ocean thermal, and biomass can be used for generation of electricity and for meeting our daily energy needs. Energy from the sun is the best option for electricity generation as it is available everywhere and is free to harness. The goal of research is to calculate the energy, engineering characteristics of solar concentrators by writing their own equations MATLAB program and compare the theoretical results with the results of the researchers was compatible.